Ethnosizing Immigrants: A Theoretical Framework - Gil Epstein; Odelia Heizler (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
Recently, Constant, Gataullina, and Zimmermann (2009) established a new method to measure ethnic identity which they called the "ethnosizer". Using information on an individual's language, culture, social interactions, history of migration, and ethnic self-identification, the method classifies that individual into one of four states: assimilation, integration, separation or marginalization. A large body of literature has emerged examining the effects of immigrants' characteristics (age, gender, education, religion, etc.) on their ethnic identity using the ethnosizer. This note presents a basic theoretical framework to shed light on the vast collection of empirical results obtained on this topic.
Keywords: 330; Ethnosizer; Immigrants; Assimilation; Integration; Separation; Marginalization